"But doth suffer a sea-change…" the need for a change of perspective for a realistic sustainability strategy in an enlarged EU. (15th July 2005) - Wolf, Frieder Otto
This paper, first, traces some main alleys for re-thinking the very underlying notions with which we tend to think about the situation with regard to the large enlargement of 2004, especially critically reflecting upon the conventional notions of "transition" and "transformation". Second, it proceeds to developing some new questions to be asked on the basis of renewed underlying notions of political interventions into variegated concrete historical processes, especially concerning the specific historical paths of development of the respective countries before, during, and after their period of Soviet dominance. Third, it presents some arguments, why these variegated situations in the history of new member countries or future accession countries present, at once, a specific challenge and a significant chance for an approach in terms of a complex and integrated strategy of sustainable development, allowing for many specific strategies to be implicit in one overarching and second order strategy defining a practice of governance for sustainable development. On this basis it outlines a new approach to what it calls the task of a second order governance, defining a sustainability strategy to identify – to "unearth" and to "revive" – those innovative lines and traditions within the CEE and CIS countries which are specifically related to such an attitude of looking for windows of opportunity for concrete moves approaching objectives of sustainable development – i.e., for looking systematically and comprehensively for constructive alternatives to the unilateralism of the leading powers and hegemonic strata which have defined the simplified models in place.